2011
DOI: 10.1248/jhs.57.532
|View full text |Cite
|
Sign up to set email alerts
|

Safety Study of Yeast Hydrolysate with below 10 kDa Molecular Weight in Animal Models

Abstract: The aim of this study was to obtain data on the safety of yeast hydrolysate with below 10 kDa molecular weight. The acute [at a single dose of 5000 mg/kg body weight (BW)] and subacute (at a dose of 1000 mg/kg BW for 14 consecutive days) oral toxicity of yeast hydrolysate from Saccharomyces cerevisiae was assessed in Sprague-Dawley (SD) rats. The yeast hydrolysate acute treatment via the oral route at the dose of up to 5000 mg/kg did not produce any signs of toxicity or death in the rats. The yeast hydrolysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Even in a previous study with single-dose and repeated-dose administration (for 14 days) of the test compound, intergroup differences in weight gain, dietary intake, and drinking water intake were not significant. Furthermore, in the subacute toxicity test, the weight gain in the male rats significantly differed from the control group ( Jung et al, 2011 ). DNF-10 was developed as an anti-obesity material and its weight loss effects have been reported previously ( Kim et al, 2004 ; Jung et al, 2009 ; Jung et al, 2012 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Even in a previous study with single-dose and repeated-dose administration (for 14 days) of the test compound, intergroup differences in weight gain, dietary intake, and drinking water intake were not significant. Furthermore, in the subacute toxicity test, the weight gain in the male rats significantly differed from the control group ( Jung et al, 2011 ). DNF-10 was developed as an anti-obesity material and its weight loss effects have been reported previously ( Kim et al, 2004 ; Jung et al, 2009 ; Jung et al, 2012 ).…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, yeast hydrolysates have been reported to exhibit physiological active functions through the regulation of hormones via neurotransmitter expression in the brain ( Jung et al, 2009 ). Although previous evaluations of the safety of yeast hydrolysates have shown that these compounds have various physiological activities ( Jung et al, 2010 ; Jung et al, 2011 ), single- and repeated-dose toxicity tests (acute and subacute toxicity tests, respectively) are required because new standards have been applied due to changes in the external environment. Therefore, this study was aimed at evaluating the safety of yeast hydrolysate, DNF-10, through single- and repeated-dose toxicity tests with doses of 5,000 and 1,000 mg, respectively.…”
Section: Introductionmentioning
confidence: 99%